Automated Titration of Vasopressor Infusion Using a Closed-loop Controller: In Vivo Feasibility Study Using a Swine Model. (March 2019) - Joosten, Alexandre; Delaporte, Amélie; Alexander, Brenton; Su, Fuhong; Creteur, Jacques; Vincent, Jean-Louis; Cannesson, Maxime; Rinehart, Joseph
Editor's Perspective: What We Already Know about This Topic: Intraoperative hypotension has been associated with adverse postoperative outcomes. A randomized controlled trial of individualized blood pressure management in patients undergoing major abdominal surgery found reduced postoperative adverse events in patients in the blood pressure management intervention group versus the standard of care group. What This Article Tells Us That Is New: In this study of pigs with normovolemic hypotension induced by administration of sodium nitroprusside, an automated closed-loop vasopressor administration device was able to maintain mean arterial pressure within 5 mmHg of 80 mmHg for 98% of the intraoperative period. This suggests that norepinephrine can be accurately titrated using an automated infusion device in order to maintain target blood pressure. Background: Multiple studies have reported associations between intraoperative hypotension and adverse postoperative complications. One of the most common interventions in the management of hypotension is vasopressor administration. This approach requires careful and frequent vasopressor boluses and/or multiple adjustments of an infusion. The authors recently developed a closed-loop controller that titrates vasopressors to maintain mean arterial pressure (MAP) within set limits. Here, the authors assessed the feasibility and overall performance of this system in a swine model. The authors hypothesized that the closed-loop controller would be able to maintain MAP at a steady, predefined target level of 80 mmHg for greater than 85% of the time. Methods: The authors randomized 14 healthy anesthetized pigs either to a control group or a closed-loop group. Using infusions of sodium nitroprusside at doses between 65 and 130 µg/min, we induced four normovolemic hypotensive challenges of 30 min each. In the control group, nothing was done to correct hypotension. In the closed-loop group, the system automatically titrated norepinephrine doses to achieve a predetermined MAP of 80 mmHg. The primary objective was study time spent within ±5 mmHg of the MAP target. Secondary objectives were performance error, median performance error, median absolute performance error, wobble, and divergence. Results: The controller maintained MAP within ±5 mmHg of the target for 98 ± 1% (mean ± SD) of the time. In the control group, the MAP was 80 ± 5 mmHg for 14.0 ± 2.8% of the time ( P < 0.0001). The MAP in the closed-loop group was above the target range for 1.2 ± 1.2% and below it for 0.5 ± 0.9% of the time. Performance error, median performance error, median absolute performance error, wobble, and divergence were all optimal. Conclusions: In this experimental model of induced normovolemic hypotensive episodes in pigs, the automated controller titrated norepinephrine infusion to correct hypotension and keep MAP within ±5 mmHg of target for 98% of management time. Abstract : In this study of pigs with normovolemic hypotension induced by administration of sodium nitroprusside, an automated closed-loop vasopressor administration device was able to maintain mean arterial pressure within 5 mmHg of 80 mmHg for 98% of the intraoperative period. This suggests that norepinephrine can be accurately titrated using an automated infusion device in order to maintain target blood pressure.